2005
DOI: 10.1016/j.physrep.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Quark–hadron duality in electron scattering

Abstract: Abstract. Quark-hadron duality addresses some of the most fundamental issues in strong interaction physics, in particular the nature of the transition from the perturbative to non-perturbative regions of QCD. I summarize recent developments in quarkhadron duality in lepton-hadron scattering, and outline how duality can be studied at future high-luminosity facilities such as Jefferson Lab at 12 GeV or an electron-hadron collider such as EPIC. I INTRODUCTIONUnderstanding the structure and interaction of hadrons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
259
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(275 citation statements)
references
References 433 publications
16
259
0
Order By: Relevance
“…Possible small variation around the scaled value in Fig. 3 suggests the validity of local duality [15,16]; however, the study of the latter is beyond the scope of this paper.…”
Section: Scaling Of the Cross Sectionmentioning
confidence: 89%
“…Possible small variation around the scaled value in Fig. 3 suggests the validity of local duality [15,16]; however, the study of the latter is beyond the scope of this paper.…”
Section: Scaling Of the Cross Sectionmentioning
confidence: 89%
“…Whilst it has been observed that the standard application of DGLAP evolution to deep inelastic structure functions can appear to be inconsistent with Bloom-Gilman duality at fixed W , this apparent conflict is resolved if one takes into account the fact that the struck quark is far-off shell in the x → 1 domain (Brodsky, 2005;Lepage and Brodsky, 1980). Underlying Bloom-Gilman duality is the assumption of quark-hadron duality; namely, a belief that one obtains equivalent descriptions of physical phenomena irrespective of whether one uses partonic or hadronic degrees-of-freedom (Melnitchouk et al, 2005;Shifman, 2000).…”
Section: E High Twist Effects and Target Mass Correctionsmentioning
confidence: 99%
“…Moments of structure functions from proton and neutron access different matrix elements of local operators within the Operator Product Expansion approach [5][6][7]. Finally, a better understanding of the phenomenon of quark-hadron duality [8,9] requires detailed studies of polarized as well as unpolarized structure functions of both nucleons in the resonance and DIS regions. While suitable free neutron targets do not exist, one can extract spin structure functions for a bound neutron using polarized nuclei like 2 H and 3 He, using some prescription to account for Fermi-motion and the effective polarization of nucleons in nuclei.…”
Section: Introductionmentioning
confidence: 99%